Measurement of Uranium Concentrations in the Soil Samples of Nineveh Province, Iraq Using CR-39 Detector - Malik H. Kheder; Hanaa N. Azeez (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
The physiological influence of radiation, which may induce cancer, makes the radioactive field vital to human health. Radon, which is hazardous to both humans and the environment, is deposited in soil via uranium decay. Extended exposure to elevated levels of alpha radiation, primarily radon, causes lung cancer. Thus, research is necessary to observe how the levels of human exposure vary. In evaluating natural exposure radiation, it is essential to control the quantity of radionuclides in the soil by determining the radioactivity level from these sources. Twenty samples of soil from different places in the Nineveh province in northern Iraq were analyzed for uranium content by the CR-39 nuclear track detector. These samples had radon concentrations ranging from 27.221 to 59.407 Bq.m-3, and the mean is 38.917 Bq.m-3. This mean value is below the level of reference limits 100 Bq.m-3 of the World Health Organization (WHO). Uranium levels ranged values from 0.129 to 0.281 ppm, with a mean of 0.182 ppm. Findings demonstrate that the natural radiations in the region are within the permissible range, as shown when comparing the results to global averages, the uranium concentration levels fell below the average of global value 2.8 ppm, and below the acceptable limit of 11.7 ppm.